Efficacy of Acupuncture on Quality of Life, Functional Performance, Dyspnea, and Pulmonary Function in Patients with Chronic Obstructive Pulmonary Disease: Protocol for a Randomized Clinical Trial - Cardoso, Renato Fleury; Lacerda, Ana Cristina Rodrigues; Lima, Vanessa Pereira; de Oliveira, Lucas Fróis Fernandes; de Oliveira, Sofia Fróis Fernandes; Araújo, Rafaela Paula; Castro, Cecylia Leiber Fernandes e; da Silva, Flávia Pereira; de Paiva, Lizânia Vieira; Dietrich, Lia; Figueiredo, Pedro Henrique Scheidt; Costa, Henrique Silveira; et al. (Journal of Clinical Medicine, 2022)
Chronic obstructive pulmonary disease (COPD) is a respiratory disease characterized by the presence of chronic airflow obstruction. Previous studies have evaluated the effect of acupuncture treatment (AT) in patients with COPD. Nevertheless, these studies show a great deal of heterogeneity in treatment protocols, having sample sizes that are too small to estimate and clarify effect size and heterogeneity in patients’ baseline. The aim of this study is to evaluate the effectiveness of acupuncture on quality of life, functional performance, dyspnea, and pulmonary function in patients with COPD. As such, patients will go through the following three phases: Phase I–pretreatment: period of subject selection and inclusion in the protocol, with an interview and performance of exams and tests as follows: Mini-Cog, dual-energy X-ray absorptiometry, spirometry, the Patient-Generated Index, Saint George’s Respiratory Questionnaire, the six-minute walk test, the London Chest Activity of Daily Living, and the COPD Assessment Test. Phase II–8 weeks of treatment, with AT 3 times a week, with two parallel groups: Group I–with 50 subjects–AT according to the recommended technical standards; Group II–with 50 subjects–Control, without acupuncture. Phase III–Continuation of AT for 8 weeks, maintaining the subjects in the previously allocated groups and following the same methodology.
Keywords: COPD; acupuncture; acupuncture therapy; acupuncture treatment; chronic obstructive pulmonary disease; health-related quality of life; quality of life